Pengenalan Refugia sebagai Pengendali Alami Hama pada Budidaya Padi Organik di Desa Ida Manggala Kabupaten Hulu Sungai Selatan: Introduction of Refugia as a Natural Pest Controller in Organic Rice Cultivation in Ida Manggala Village, Hulu Sungai Selatan Regency - Untung Santoso; Yulia Padma Sari; Hairu Suparto; Antar Sofyan; Rizka Diandra Putri; Syamsul Khairuddin (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Ida Manggala is one of the villages in Sungai Raya District where some residents cultivate rice and others practice organic rice cultivation. In organic rice cultivation, pest and disease control is carried out by natural methods, such as the use of natural enemies, crop rotation, and good cultivation techniques. One effort to increase the population of natural enemies is to plant refugia. Refugia are plants that are grown around or within rice fields to provide habitat for natural enemies of pests, such as predators and parasitoids. The purpose of this activity is to introduce the refugia system to Gapoktan partners in Ida Manggala Village and to provide training on the cultivation of several types of refugia plants to support sustainable organic rice farming. This activity is carried out through socialization, technical training, and direct practice of planting refugia around organic rice farmland owned by the village community. The conclusions obtained after this activity are as follows: (a) The knowledge and skills of rice farmers in the cultivation of refugia plants showed an increase after the implementation of the activity; (b) Participants' understanding of the benefits of refugia plants is getting better, accompanied by the ability to apply cultivation techniques that include proper land preparation, planting, and maintenance, so that it is expected to provide useful by-products.